Innovation and creativity its impact on the relationship of business ideas - Pérez Palacios, Emma Emilia (2022)
The purpose of this study is to analyze the Innovation and Creativity Capacities and their Impact on the materialization of Business Ideas of the entrepreneurs of the FCA Incubator - UNMSM, for this a mixed type of research study was applied. explanatory, correlational and transversal, which had a study sample of 43 incubated students who presented themselves at the entrepreneurial fair organized by the Incubator of the Faculty of Administrative Sciences "Ideando" in November 2018 II to which it was applied a questionnaire to measure the dimensions of the study. Taking as a more relevant conclusion that in 13 of the 15 dimensions of the creativity and innovation variable, medium levels have been obtained, only Mental Curiosity (74.4%), Constant search for ideas (51.2%) and Knowledge of Innovation processes (41.9%) have upper level. This indicates that entrepreneurs have average characteristics in terms of the study variables, and with it, more than half of the survey carry their ventures at a medium level, which if it verifies innovation and creativity is necessary for the materialization of the ventures.